Effects of Cardiotoxins on Cardiac Stem and Progenitor Cell Populations - Smith, Andrew J. (Frontiers in Cardiovascular Medicine, 2021)
As research and understanding of the cardiotoxic side-effects of anticancer therapy expands further and the affected patient population grows, notably the long-term survivors of childhood cancers, it is important to consider the full range of myocardial cell types affected. While the direct impacts of these toxins on cardiac myocytes constitute the most immediate damage, over the longer term, the myocardial ability to repair, or adapt to this damage becomes an ever greater component of the disease phenotype. One aspect is the potential for endogenous myocardial repair and renewal and how this may be limited by cardiotoxins depleting the cells that contribute to these processes. Clear evidence exists of new cardiomyocyte formation in adult human myocardium, along with the identification in the myocardium of endogenous stem/progenitor cell populations with pro-regenerative properties. Any effects of cardiotoxins on either of these processes will worsen long-term prognosis. While the role of cardiac stem/progenitor cells in cardiomyocyte renewal appears at best limited (although with stronger evidence of this process in response to diffuse cardiomyocyte loss), there are strong indications of a pro-regenerative function through the support of injured cell survival. A number of recent studies have identified detrimental impacts of anticancer therapies on cardiac stem/progenitor cells, with negative effects seen from both long-established chemotherapy agents such as, doxorubicin and from newer, less overtly cardiotoxic agents such as tyrosine kinase inhibitors. Damaging impacts are seen both directly, on cell numbers and viability, but also on these cells' ability to maintain the myocardium through generation of pro-survival secretome and differentiated cells. We here present a review of the identified impacts of cardiotoxins on cardiac stem and progenitor cells, considered in the context of the likely role played by these cells in the maintenance of myocardial tissue homeostasis.